NCOA2 promotes lytic reactivation of Kaposi’s sarcoma-associated herpesvirus by enhancing the expression of the master switch protein RTA - Wei, Xiaoqin; Bai, Lei; Dong, Lianghui; Liu, Huimei; Xing, Peidong; Zhou, Zhiyao; Wu, Shuwen; Lan, Ke (PLoS pathogens, 2019)
Reactivation of Kaposi's sarcoma-associated herpesvirus (KSHV) is important for persistent infection in the host as well as viral oncogenesis. The replication and transcription activator (RTA) encoded by KSHV ORF50 plays a central role in the switch from viral latency to lytic replication. Given that RTA is a transcriptional activator and RTA expression is sufficient to activate complete lytic replication, RTA must possess an elaborate mechanism for regulating its protein abundance. Previous studies have demonstrated that RTA could be degraded through the ubiquitin-proteasome pathway. A protein abundance regulatory signal (PARS), which consists of PARS I and PARS II, at the C-terminal region of RTA modulates its protein abundance. In the present study, we identified a host protein named Nuclear receptor coactivator 2 (NCOA2), which can interact with RTA in vitro and in vivo. We further showed that NCOA2 binds to the PARS II domain of RTA. We demonstrated that NCOA2 enhances RTA stability and prevents the proteasome-mediated degradation of RTA by competing with MDM2, an E3 ubiquitin ligase of RTA that interacts with the PARS II domain. Moreover, overexpression of NCOA2 in KSHV-infected cells significantly enhanced the expression level of RTA, which promotes the expression of RTA downstream viral lytic genes and lytic replication. In contrast, silencing of endogenous NCOA2 downregulated the expression of viral lytic genes and impaired viral lytic replication. Interestingly, we also found that RTA upregulates the expression of NCOA2 during lytic reactivation. Taken together, our data support the conclusion that NCOA2 is a novel RTA-binding protein that promotes RTA-driven lytic reactivation by increasing the stability of RTA, and the RTA-NCOA2 positive feedback regulatory loop plays an important role in KSHV reactivation.